Novel compound heterozygous variants of TBXAS1 presenting with Ghosal hematodiaphyseal dysplasia treated with steroids. Issue 3 (17th February 2021) - Kim, Sun Young; Ing, Alexander; Gong, Shunyou; Yap, Kai Lee; Bhat, Rukhmi
Abstract: Background: Homozygous or compound heterozygous pathogenic variants in the thromboxane A synthase 1 ( TBXAS1 ) gene are associated with Ghosal hematodiaphyseal dysplasia (GHDD) which is characterized by defective hematopoiesis and increased bone density of long bones. Methods: Patients 1 and 2 are identical twins, who presented with red blood cell transfusion‐dependent normocytic anemia and thrombocytopenia with bone marrow fibrosis and cortical bone thickening of long bones on plain radiograph. To clarify the etiology of their anemia and thrombocytopenia, whole blood was used for the DNA extraction and analyzed using next‐generation sequencing (NGS) on an in‐house bone marrow failure syndrome panel. Results: The NGS results indicated that these two patients carried two heterozygous variants in TBXAS1, exon7, c.583_584del, p.Ala195Leufs*12, and exon12, c.1420G>T, p.Gly474Trp, which were inherited from their mother and father, respectively. Patients 1 and 2 have been on chronic oral steroids with normalization of hemoglobin and platelet count after steroid initiation. Patient 3 is their sister who has normal blood counts but also has the same variants in TBXAS1 as her brothers. Radiographs showed cortical bone thickening and she has not required any treatment or transfusion. Conclusion: We report three Caucasian siblings from non‐consanguineous parents with novel compound heterozygous variants of TBXAS1 presenting with the phenotypes of GHDD. These three cases illustrate the variable clinical expressivity of the GHDD from two‐compound heterozygous pathogenic variants of TBXAS1 . Abstract : We report three Caucasiion siblings from non‐consanguineous parents with novel compound heterozygous variants of TBXAS1 presenting with phenotypes of GHDD. Patient 1 and 2 are identical twins, who presented with red blood cell transfusion dependent normocytic anemia and thrombocytopenia with bone marrow fibrosis and cortical bone thickening of long bones on plain radiograph. Patient 3 is their sister with normal blood counts but cortical bone thickening on radiograph who has not required any treatment. These three cases illustrate the variable clinical expressivity of the GHDD from two‐compound heterozygous pathogenic variants of TBXAS1.